Improving teacher competence through the new Malaysian Teacher Standards: Exploring the challenges for teacher educators - Goh, Pauline Swee Choo (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Teacher competence is recognised as an important requisite to improve students‟ academic performance and their experiences of schooling. The current strategy in Malaysia to improve this competency and outcomes of education culminated in the articulation of the Standard Guru Malaysia or the Malaysian Teacher Standards (MTS). Introduced in December 2009, the MTS is to establish high teaching standards and sets out to recognise accomplished teaching among the teaching profession. Although proponents of the standards have welcomed its introduction, this article argues that the MTS poses significant challenges for teacher educators as they set out to train new teachers to begin teaching in ways that are congruent to the standards. The article claims that the new MTS represent the standards towards which teacher educators must now aim for. In fact, this is an intentional element embedded in the MTS. The Malaysian government hopes that by initiating standards by which teachers are to be appraised upon, will in turn effect changes in how they are prepared. However, less understood are the challenges it presents for the teaching institutions. This article presents various challenges (and possibilities) for teacher educators. Although the article lacks empirical base for examining these issues, due to the newness of the MTS, it offers instead a logical analysis based on the authors‟ own (and others‟) experiences to illuminate the issues.